Effects of Shade on the Growth and Mineral Nutrition of Tropical Grasses in Silvopastoral Systems - Cruz, Pablo; Sierra, Jorge; Wilson, John R; Dulormne, Maguy; Tournebize, Regis (Annals of Arid Zone, 2016)
Interactions between tree and grass strata in silv.opastoral systems have been studied for a large number of species and environmental conditions. In tropical environment the increase of growth andlor mineral nutrition of the grass stratum due to tree shade has been very often reported. This effect has been observed even for non-leguminous tree component and under artificial shading, and occurs most frequently when water and nitrogen are limiting factors for grass growth. This paper reviews the literature on morphogenetic and trophic responses of tropical ,C4 grasses to shading, as wen as on the ecological, physiological and physical mechanisms involved in these responses. It is concluded that shade enhances the availability of nutrients in the soil, which concerns the chemical andlor physical fertility. The principal processes involved are: (i) recycling of nitrogen fixed by legume trees via leaf-root-nodules decomposition andlor animal excreta, (ii) changes in microclimatic conditions by shade, favoring the biological activity of the soil, and (iii) transfer of nutrients absorbed by trees from the deeper layers of the soil to the surface via leaf drop andlor animal excreta. The needs and perspectives for future research are discussed.